Angiogenesis, Cancer, and Vascular Aging - Moriya, Junji; Minamino, Tohru (Frontiers in Cardiovascular Medicine, 2017)
Several lines of evidence have revealed that the angiogenic response to ischemic injury declines with age, which might account for the increased morbidity and mortality of cardiovascular disease (CVD) among the elderly. While impairment of angiogenesis with aging leads to delayed wound healing or exacerbation of atherosclerotic ischemic diseases, it also inhibits the progression of cancer. Age-related changes of angiogenesis have been considered to at least partly result from vascular aging or endothelial cell senescence. There is considerable evidence supporting the hypothesis that vascular cell senescence contributes to the pathogenesis of age-related CVD, suggesting that vascular aging could be an important therapeutic target. Since therapeutic angiogenesis is now regarded as a promising concept for patients with ischemic CVD, it has become even more important to understand the detailed molecular mechanisms underlying impairment of angiogenesis in older patients. To improve the usefulness of therapeutic angiogenesis, approaches are needed that can compensate for impaired angiogenic capacity in the elderly while not promoting the development or progression of malignancy. In this review, we briefly outline the mechanisms of angiogenesis and vascular aging, followed by a description of how vascular aging leads to impairment of angiogenesis. We also examine potential therapeutic approaches that could enhance angiogenesis and/or vascular function in the elderly, as well as discussing the possibility of anti-senescence therapy or reversal of endothelial cell senescence.